Acting on Multiple Stages: How Musical Actors Construct Their Labour-Market Vulnerability and Resilience - Ibert, Oliver; Schmidt, Suntje (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
This paper takes a social-constructionist approach to the terms vulnerability and resilience in order to test their analytical potential within the frame of an empirical spatial-science study. The empirical object was deliberately chosen from a field untypical for vulnerability analyses: the volatile labour markets for musical actors. The paper draws on qualitative interviews to trace the actors’ construction of labour-market related uncertainties, mainly caused by labour-market dynamics as well as institutional and territorial mismatches. Barely any resilience strategies exist for these forms of vulnerability. As a result, musical actors construct multiple identities from their bodies and talents, which they use in a targeted way within different spatial and social contexts. Two forms of network governance are additionally established to attenuate some of the competitive mechanisms. From a spatial viewpoint, these practices constitute transient, multi-local activity spaces in the labour market in which action is more effective when combined with a relatively stable home base.
Keywords: Vulnerability; Resilience; Creative economy; Musical; Labour market